DIMENSI SOSIO-EKONOMI DAN IMPLIKASI KEBIJAKSANAAN PEMUKIMAN PERAMBAH HUTAN* - Riwanto Tirtosudarmo (Populasi, 1993)
The problems of settlement concerning "forest explorers" (slash and burn cultivators) have become increasingly interesting in the last few years, particularly since many countries in the world have been propagandizing reforestation throughtout the world. This study is discussing various problems relating with forest explorations in Indonesia, the socioeconomic dynamics, the settlement policy to explorers, and the constraints of its related implementation policies.Several significant points proposed in the study are that whatever the efforts or the program selected by the decision makers of this field of study, they have to realize that the phenomenon of forest explorers and their related problems is a symptom of a more basic problem, which is the disparity of income distribution among groups as well as among regions in Indonesia.